Ubiquinone Binding and Reduction by Complex I—Open Questions and Mechanistic Implications - Galemou Yoga, Etienne; Schiller, Jonathan; Zickermann, Volker (Frontiers in Chemistry, 2021)
NADH:ubiquinone oxidoreductase (complex I) is the first enzyme complex of the respiratory chain. Complex I is a redox driven proton pump that contributes to the proton motive force that drives ATP synthase. The structure of complex I has been analyzed by X-ray crystallography and cryo-EM and is now well described. The ubiquinone (Q) reduction site of complex I is buried in the peripheral arm and a tunnel like structure is thought to provide access for the hydrophobic substrate from the membrane. Several intermediate binding positions for Q in the tunnel were identified in molecular simulations. Structural data showed binding of native Q molecules and short chain analogues and inhibitors in the access pathway and in the Q reduction site, respectively. We here review current knowledge on the interaction of complex I with Q and discuss recent hypothetical models for the coupling mechanism.